Sustainable choices of plant-based (‘super’) foods: examining the consumption patterns of German consumers on avocados - Ohlau, Marlene; Huning, Sophie Christine; Spiller, Achim (Frontiers in Nutrition, 2023)
This paper aims to better understand consumer awareness of the environmental impact of plant-based (‘super’-) foods, using avocados as an example. Since all food production impacts the environment, both meat-based and plant-based, there is scope for more sustainable food choices. Avocados have positive health properties while being considered critically for the potential negative environmental impact of their production. This study examines the avocado consumption behaviour of German consumers and the extent to which knowledge and dietary patterns are related to this. Data from 372 respondents from Germany were collected through an online consumer survey. Bivariate comparisons for avocado consumption and logistic regression analyses were performed to explore avocado consumption behaviour. The frequency of avocado consumption among respondents was moderate, averaging once per month. Avocado consumption was related to a flexitarian diet, older age and higher income, and urban dwellers. Knowledge of the environmental impacts of avocado cultivation had no influence. Respondents’ self-assessed knowledge about avocados was low. To help consumers in making conscious, sustainable choices for plant-based foods, it is necessary to provide accessible and comparable information on the environmental impact of food products. However, further life cycle assessments on avocado production are clearly needed in order to produce valid information material. A flexitarian diet with reduced consumption of animal foods is an important prerequisite for environmental sustainability. Drawing attention to environmentally friendly plant-based food choices for flexitarian consumers could further encourage them to become food innovators for a healthy planet by reducing climate impact, land use, and energy and water consumption.